Anti-Cancer and Acute Toxicity Activity of Benzo[e]Indol-2- Ylidene)-3 -(4-Methoxyphenyl) Imino Propanal - Ahmed Jasim Mohammed Gawi; Walaa Najm Abood; Fadhil Lafta Faraj (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The new indole Schiff base compound benzo[e]indol-2-ylidene)-3-(4-methoxyphenyl)iminopropanal](2P)was investigated for antioxidant, toxicity and anti-tumor ability for A547 cell, PC3 celland WRL 68 cell.Results: 2P has antioxidant ability for IC50 (75 µg/mL) compared with control ascorbic acid (27 µg/mL).Antitumor ability to 2P for A547 cell and PC3 cell were decreased significantly after treated with 2P in dosedependent manner at 24,48 and 72 hours, while no toxicity effect on the WRL 68 cell. The antitumor effectwas through accelerated apoptosis, the alteration in nuclear morphology. Increasing in the cells membranepermeability, decreasing in the nucleus intensity with the increasing of concentration of 2P compound wasobserved.MMP is disturbed in the apoptosis by forming of permeability and the result was showed that 2P activatedrelease cytochrome c significant higher than control.2P break down the cell cycle progress in G1 phase (P<0.05) compared with control. Conclusion: this result was conducted the new 2P compound has antioxidantand antitumor ability that may be used 2P a new anticancer drug.